Controls on the Isotopic Composition of Precipitation in the South‐Central United States. Issue 14 (31st July 2019) - Sun, Chijun; Shanahan, Timothy M.; Partin, Judson
Abstract: The processes that control the isotopic composition of precipitation in the midlatitudes are complicated, but can provide valuable insights into precipitation‐generating processes and are critical for interpreting stable isotope‐based paleoclimate records. In this study, we investigated the controls on changes in the isotopic composition of rainwater in central Texas using a combination of existing monthly stable isotope data from the global network of isotopes in precipitation and 20 months of event‐based rainwater collection from Austin, TX. We find that the strongest control on the isotopic composition of precipitation is the varying proportion of convective and stratiform rainfall, with other factors such as precipitation amount, temperature, and storm track playing a secondary role. Isotopic values are generally lower in the cold season than the warm season precipitation because cold season precipitation is predominantly stratiform often associated with a northerly storm track. However, the majority of the precipitation in the south‐central United States occurs during the warm season in association with mesoscale convective systems (MCSs) that are fed with moisture by the southerly winds. MCSs are characterized by a combination of a leading edge of organized deep convection and trailing stratiform precipitation. Stronger MCSs tend to contain higher proportions of stratiform rainfall and, as a result, have more isotopically depleted values. Therefore, changes in the stable isotopic composition of rainfall may be interpreted as reflecting changes in the intensity of MCS. Key Points: Gulf of Mexico is the main moisture source for precipitation in the south‐central United States Rain type shows the strongest control on the isotopic composition of precipitation Lower isotopic values and lower convective fractions are associated with stronger mesoscale convective systems in the warm season